The duration of filled pauses and prolongations in northern and southern dialects of Spanish - Pálvölgyi, Kata Baditzné (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2020)
This research focuses on the prosodic patterns of hesitations contrasted in Northern and Southern dialects of European Spanish, more precisely, on their duration. A corpus of 200 spontaneous utterances has been compiled (including 100 utterances from the northern dialects and 100 utterances from the southern ones, produced by 16 male and 16 female informants, respectively). The analysis has been carried out following the standardization protocol offered by Cantero (2019), in which the representative values of duration (in seconds) are taken for each syllable, and then these values undergo a process of standardization, in order to be comparable objectively and speaker-independently. Due to difficulties in establishing exact syllable boundaries in Spanish, it is not the relative duration of the syllables, but rather the relative duration of the distances between intensity peaks which is compared. It is expected that certain “neutral” hesitations –lengthenings and filled pauses with no specific communicative function – show durational differences in the examined dialects, as Southern dialects are considered to be of higher speech rate due to frequent segment elision than northern ones. This would imply that the relative duration of the examined hesitation phenomena with respect to its context– supposedly of the same absolute duration as in the northern dialects – is longer in the southern dialects. According to the results, nevertheless, Southern dialects present shorter absolute duration also in case of hesitation phenomena, and thus relative duration of hesitation phenomena with respect to their context coincide in the two examined Spanish variants.